The Importance of Artificial Intelligence in Sales Management in the B2B Industry (Journal of Artificial Intelligence & Research, 2024)
The business-to-business (B2B) industry is highly competitive, and sales management plays a crucial role in achieving success. Sales managers are responsible for driving revenue growth, developing, and implementing sales strategies, managing customer relationships, and optimizing the sales process. In recent years, the emergence of artificial intelligence has revolutionized various industries, and its impact on sales management in the B2B sectors undeniable.